2007
DOI: 10.1002/ajpa.20562
|View full text |Cite
|
Sign up to set email alerts
|

Potential applications of urinary C‐peptide of insulin for comparative energetics research

Abstract: The study of comparative energetics offers a valuable way to identify broad ecological principles and assess the functional significance of energetic adaptations during the course of evolution. Yet, the quantification of energetic status for nonhuman primates under natural conditions remains one of the most challenging aspects of comparative energetics research. Here, we report on the development of a noninvasive field method for measuring energetic status in great apes, humans, and possibly other nonhuman pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
60
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 64 publications
4
60
1
Order By: Relevance
“…This study joins other recent research validating the efficacy of Cpeptide for measuring energetic condition in apes (Deschner et al, 2008;Emery Thompson and Knott, 2008;Sherry and Ellison, 2007). These data provide the first thorough test of the method for chimpanzees, applying a large sample to illustrate that basic measures of dietary quality account for a substantial portion of the variation in male C-peptide concentrations.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…This study joins other recent research validating the efficacy of Cpeptide for measuring energetic condition in apes (Deschner et al, 2008;Emery Thompson and Knott, 2008;Sherry and Ellison, 2007). These data provide the first thorough test of the method for chimpanzees, applying a large sample to illustrate that basic measures of dietary quality account for a substantial portion of the variation in male C-peptide concentrations.…”
Section: Discussionsupporting
confidence: 63%
“…Here we show that known habitat differences between two chimpanzee home ranges in Kibale National Park are reflected in the C-peptide levels of community members. Sherry and Ellison (2007) similarly demonstrated that captive chimpanzees had higher C-peptide levels than their energeticallystressed, wild counterparts. In addition to providing a metric for energetic variation between communities, these findings demonstrate that C-peptide levels in apes reflect individual variation in energetic condition.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations